Childhood Experiences as determinant of Antisocial Behaviours among Basic School Pupils in Oyo State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2026)
The study examined how childhood experience determined antisocial behaviour among basic school pupils in Oyo state, Nigeria. Specifically, the study aimed to identify the level of antisocial behaviour, assessed prevalent childhood experiences among basic school children in Oyo State, Nigeria. A descriptive survey design was employed. The research employed multi-stage sampling procedures incorporating simple random sampling and a baseline method. From a total population of 2503 basic school, a sample of 96 schools were selected across 24 local government areas, comprising a total sample size of 812 pupils across all selected schools. The "Childhood Experiences, Questionnaire (CESQ) (r = 0.893) was used to gather information. One research question and one hypothesis were raised and tested. Data were analysed using frequency, percentage, mean, standard deviation, Pearson Correlation, and Multiple regression analysis.   The findings revealed bullying victimisation experiences being most prevalent. Females exhibited higher antisocial behaviour (t= 92.170, X̅ = 2.62017, p< 0.05) than males (t = 77.959, X̅ = 2.39682, p< 0.05).  The study provides a comprehensive understanding of antisocial behaviour among basic school pupils in Oyo State, Nigeria. revealing the complex interplay between gender differences. Implementing school-based behaviour management, peer mediation, and empathy-building activities is recommended to reduce subtle antisocial behaviours.